Overview Metode Fitoremediasi Terhadap Penyerapan Logam Berat Pada Air Terkontaminasi Menggunakan Jenis Tumbuhan Air - Fitra Kurniawan (Retii, 2022)
Heavy metal contamination in the environment is a serious problem for public health that has an impact on sustainability and human survival. As a result, heavy metal contamination of water causes many diseases in humans such as carcinogenic diseases and other diseases. To solve this problem, there are a large number of new technologies in dealing with heavy metal pollution in water. Phytoremediation with aquatic plants to remove heavy metal contaminants, phytoremediation has been widely used to restore pollution in water. The purpose of this study is to provide general information about phytoremediation and the use of aquatic plants for phytoremediation of heavy metals from the environment. By discussing applied science and environmental engineering to produce sustainable products to improve water quality. This study shows the effectiveness of aquatic plant species and compares the absorption of heavy metals at different concentrations. Based on the literature study, there are various types of aquatic plants with efficient phytoremediation capabilities and need to be studied from different perspectives to make contaminated water phytoremediation an environmentally friendly method.